Exploring markets: Non-Fungible Token - Daniel Weber (IU Internationale Hochschule, 2022)
– Exploring Markets" is a paper series discussing niche markets with interesting characteristics. The paper on hand focuses on the market for Non-Fungible Token (NFT) which are transferrable rights of ownership to unique digital assets. NFTs are based on blockchain technology and are traded with cryptocurrencies primarily on specialized marketplaces. In 2021 record breaking auctions of expensive NFTs got mainstream attention, whereas a decreasing trade volume at the start of 2022 might indicate challenges in market adoption for this new technology. The paper discusses specific characteristics of NFTs, use cases and associated problems.
Keywords: Z19; 650; Market Study; NFTs; Non-Fungible Token